Biological Flora of the British Isles: Crassula helmsii. (20th February 2020) - Smith, Tim; Buckley, Phil
Abstract: This account presents information on all aspects of the biology of Crassula helmsii (Kirk) Cockayne (New Zealand Pygmyweed, Australian Swamp Stonecrop) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, history, and conservation. Crassula helmsii is an invasive aquatic macrophyte originating from Australia and New Zealand. The first naturalized population was recorded in Britain in 1956. All British specimens appear to represent a single lineage. DNA analysis indicates that British specimens originate from Australia. Crassula helmsii is capable of growing in a wide range of lentic freshwater and riparian habitats. It may grow as free floating, submerged, emergent or terrestrial forms. Morphology can differ markedly on the same stem. Flowers are produced, but with no known pollinators outside of its native range. Reproduction is thought to be predominantly by asexual methods outside Australia and New Zealand, through stem fragmentation and dispersal. Seed germination outside the native range appears to be very rare and poorly understood. Crassula helmsii has been and still is controlled by active management because of fears that its capacity to produce monocultures will lead to loss of biodiversity in the plant communities it invades. Evidence for species losses due to colonization by C.  helmsii is rather anecdotal, although suppression of native biomass through competition has been reported. No consistently effective control procedures have been identified. Abstract : Crassula helmsii is an invasive, non‐native aquatic macrophyte from Australasia that has naturalized in Britain. There is concern about its rapid spread because its dense stands were perceived to cause species loss by competitive exclusion. This is reflected in the novel range of control methods that have been tried, but ultimately without success. Evidence for native diversity losses is rather anecdotal, and as control is often unattainable and can leading to greater impact than the invader itself, control has become less widely adopted.